Super Multi-View Near-Eye Display Based on Collimated Images From Waveguides - Yiping Lin; Lilin Liu; Dongdong Teng (IEEE Access, 2025)
Waveguides have been used as combiners for near-eye display in conventional three-dimensional (3D) display, guiding an image to each eye of the viewer by total reflection. Such near-eye displays suffer from manufacturing complexity of said exit pupil expansion (EPE), and Vergence-accommodation Conflict (VAC) inherent to the one-image-one-eye display mechanism. In this paper, a head-mounted-display augmented reality (HMD-AR) is proposed for simultaneously settling these two problems. At a time-point, lights from a display panel are transformed into a bundle of paralleling light beams, and guided to corresponding eye by a waveguide without EPE, as a collimated image. Guiding multiple such collimated images to each eye along different paths sequentially, a VAC-free Super Multi-view (SMV) near-eye display gets implemented. The proposed waveguide without EPE avoids the manufacturing complexity of EPE waveguide that requires multiple reflection planes with different coupling output coefficients. A prototype system with two geometric waveguides is set up for concept demonstration, obtaning a field of view (FOV) of $10.2^{° }× 14^{° }$ and a depth of field (DOF) of 1500mm. A large FOV is expected experimentally when diffractive waveguides are adopted in the further work.